OPTIMIZING ORGANIZATIONAL CAPABILITIES THROUGH THE INTEGRATION OF STRATEGIC MANAGEMENT AND HUMAN RESOURCEPERFORMANCE - Dahlia Amelia; Yenny Dwi Artini; Gina Novianti Rahayu; Hery Purnomo; Badrus Zaman (CV. Adiba Aisha Amira, 2025)
Optimizing organizational capabilities by integrating strategic management and human resource performance is paramount in contemporary organizational dynamics. This study delves into the synergistic relationship between strategic management strategies and human resource performance to enhance organizational effectiveness. The research explores the contextual factors influencing this integration and assesses its impact on operational efficiency, innovation, and customer relations. Through a comprehensive literature review and analysis, the study identifies critical influencing factors, including leadership practices, organizational culture, management information systems, and skill development. The findings underscore the transformative potential of aligning strategic goals with human resource practices, fostering a culture of collaboration, and leveraging technological infrastructure. The implications of this integrated approach are discussed in the context of practical organizational management, offering valuable insights for leaders and practitioners navigating the complexities of the modern business landscape.